UPAYA MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPLANASI DAN HASIL BELAJAR BAHASA INDONESIA DENGAN METODE INKUIRI PADA SISWA KELAS XI IPS 1 SMA NEGERI 3 METRO - Kesuma, Cik Ayu (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2020)
The result of skill and learning becoming by write explanation methode inquity XI IPS 1 SMAN 3 Metro. Data method by observation, document,and interview (test and non test). Skill texs explanation prasiklus 79,25, siclus I to 96,83 increased 17,58%, the result of prasiklus 5 to siklus I become 7, increased 2%. Skill write texs explanation by siklus II become 108,91, increased 12,08%, the resulth of learning siclus I rates 7 a,d siklus II rates 8, increased 1%. Siklus III skill write tex explanation become 200,16, increased 91,25%, the result of leaning score 9, increased 1%. The conclusion: skill tex explanation prasiklus rates 79,25%, at siklus I score 96,83%, siclus II score 108,91. And siclus III score 200,16%. The result learning praciklus 5, siclus I become 7, siclus II,8, and siclus III become 9, the rates from praciklus 2%, siklus I to siclus II become 1%, and siclus III be 1%.